Rock mechanics in petroleum industries and the importance to wellbore stability - K. S., Surej (1998)
The petroleum that also means "rock-oil" could not exist under the ground without reservoir rock be its sandstone, limestone, shale or granite. Therefore, understanding the rock characteristics and its behaviour is primarily important before the designing phase of a petroleum field. Knowing that most of the petroleum fluid will situated in sandstone, the emphasation would focus on this type of rock. The basic properties such as porosity, permeability, density, compressive strength, tensile and shear strength are need to be defined and understood, and the relationship among them should be identified. In this research paper, all rock properties and behaviour has been highlighted and the relationship between them has been explained. The problem related to the rock, e.g. shale swelling, drilling, pipe stuck, wellbore stability and sand production problem also have been discussed. The wellbore stability then been focused and related experimental work results presented. The perforation parameter and wellbore geometry have been varied to see the effects of rock stress on the wellbore stability. The results show that the rocks mechanics aspect must be considered in the designing phase of a petroleum field to avoid excessive money spending to threat the petroleum wells and to optimized the production. Therefore, the rock properties and behaviour should be understood in details before the designing period. From experimental works, it was found that the perforation parameters habe a great influence on the wellbore stability and sand production due to the stress redistribution depending upon the rock properties and behavior. The higher is the shot density, the lower will be the wellbore stability and increased sand production problem. The spiral pattern gave the best stability followed by inplane and inline patterns.